Bacterial community structure in natural marine biofilms and the corrosion of carbon steel - Machuca, Laura; Bailey, Stuart; Gubner, Rolf; Watkin, E.; Ginige, M.; Kaksonen, A. (The Australasian Corrosion Association Inc, 2011)
The application of molecular tools to the investigation of microbiologically influenced corrosion (MIC) has become crucial in the advancement of understanding the complexity and mechanisms of microbial interactions with materials and the environment. In this study, carbon steel specimens were evaluated for MIC under laboratory closed conditions by conducting corrosion tests and biofilm community structure analysis. Material coupons were immersed in natural seawater under aerobic and anaerobic conditions for up to 4 weeks where natural marine biofilms were allowed to develop. Experimental controls consisted of tests using aerobic and anaerobic filter-sterilized seawater. All experiments were carried out at 20ºC. Corrosion of carbon steel specimens was assessed using weight loss measurements, surface inspection, pit profile analysis and surface roughness measurements. The bacterial community structure of biofilms on the carbon steel surfaces was characterized using a molecular microbiology approach. Total DNA was extracted from biofilms and used as a template for amplification of 16S rRNA genes followed by denaturing gradient gel electrophoresis (DGGE) and DNA sequencing. Results are presented to show the diversity in microbial communities in biofilms covering carbon steel surfaces. In addition, these data show the relationship between carbon steel corrosion and biofilm community structure changes associated with the presence and absence of oxygen in seawater.